Effect of aromatherapy on the quality of sleep in ischemic heart disease patients hospitalized in intensive care units of heart hospitals of the Isfahan University of Medical Sciences - Moeini, Mahin (Medknow Publications Pvt Ltd, 2010)
BACKGROUND: Sleep disorder is one of the common problems patients face in ICU and CCU and it is usually treated by sleeping pills. Nowadays, the complementary medicine is highly considered because of its effectiveness and safety. Aromatherapy is one of the holistic nursing cares which sees human beings as a biological, mental and social unit while the psychological dimension has the central role. Each of these dimensions is dependent on each other and is affected by each other. Therefore, it is fundamental for nurses to provide aromatherapy in their clinical performance. Aromatherapy helps treatment of diseases by using vegetable oils and it seems to be effective in reducing sleeplessness. METHODS: This was a clinical trial on 64 patients (male and female) hospitalized in CCU in Al-zahra and Chamran hospitals. The intervention included 3 nights, each time 9 hours aromatherapy with lavender oil for the experiment group, while the controls received no intervention. Both groups filled out the SMHSQ that includes 11 items to assess sleep quality before and after intervention. RESULTS: Data analysis showed that the mean scores of sleep quality in the two groups of experiment and control were significantly different after the aromatherapy with lavender oil (p < 0.001). CONCLUSIONS: Quality of sleep in ischemic heart disease patients was significantly improved after aromatherapy with lavender oil. Therefore, using aromatherapy can improve the quality of their sleep and health.